The Temporal Change of the Effects on Land Use and Geomorphological Units of Urban Development Process in Sakarya Province - (:unkn) unknown (MARMARA UNIV, 2016)
In recent years, rapid increase has caused cities to expand in an unplanned and uncontrolled way face infrastructure problems. Expansion in urban areas also lead important changes on land use and had on negative effects on natural ecosystems. Therefore, studies during and after development of the cities has great importance for estimating future status of the cities, reducing environmental effects and sustainable planning. Aim of this study is determine the interaction between land use and geomorphological with urban development in Sakarya province using Geographical Information Systems and Remote Sensing. Data obtained by classifying dated years 2000 and 2014 Landsat images having 15 m spatial resolution to determine urban development. Main land cover changes occurred in Sakarya for 10-15 years; agricultural areas occupied by settlements and forest areas replaced by agricultural areas. Forest and shrub areas has shrunk while residential areas enlarged in consequence of population growth and tourism activities. Spreading of settlements over coastal areas causes degradation of the natural characteristics of the coast. It is concluded by this study that urban development in Sakarya province has significant pressure on current land use and geomorphological units. This negative change of urban growth in Sakarya should be evaluated according to plan and it is necessary to have sustainable land use model.
Keywords: Land use; geographic information systems (GIS); urban development; Sakarya; remote sensing (RS)